Effect of ultrasound on oil recovery from crude oil containing sludge. Issue 11 (12th May 2019) - He, Shilong; Tan, Xicheng; Hu, Xin; Gao, Yingxin
ABSTRACT: To recover oil from crude oil containing sludge is still a research hot topic from the view of sustainability, in which ultrasonic has been proven to be an efficient and environment friendly technique. However, the effect of sludge characteristic on ultrasonic-assisted oil recovery efficiency is little known. In this study, the analysis of variance (ANOVA) was conducted based on six types of crude oily sludge with hydrophilicity and lipophilicity separately and five different ultrasonic operation factors (ultrasonic power (A), frequency (B), time (C), initial temperature (D) and pH (E)). The results showed that the oil recovery efficiency was mainly affected by the ultrasonic power and hydrophilicity of sludge (the highest 92% of oil recovery rate was achieved with the ultrasonic power of 240 W and hydrophilic sludge). Moreover, the wettability, decreased average particle size and increased specific surface area of sludge were found after ultrasonic treatment. Besides, changes in the oil component, such as the decrease of asphaltenes along with an increase of saturates, were also further observed. Therefore, the findings in this study can provide technical support for the practical application of ultrasonic technology in different kinds of oily sludge treatment.